Circadian clocks and their role in kidney and eye diseases across organ systems - Chen, Xiuli; Zhang, Wenxiao; Gu, Yue; Huang, Shenzhen (Frontiers in Physiology, 2025)
Circadian rhythms, the body’s intrinsic 24-h cycles, regulate essential physiological processes across multiple organ systems. Disruptions in these rhythms are increasingly recognized as significant contributors to chronic kidney disease and ocular diseases such as glaucoma, dry eye disease, and diabetic retinopathy. This review examines the interconnections between circadian rhythms in kidney and eye health, focusing on shared pathological pathways including oxidative stress, inflammation, and fibrosis. Current therapeutic strategies such as chronotherapy, light therapy, and time-restricted feeding show promise in mitigating disease progression by restoring circadian alignment. This review emphasizes integrated circadian-focused treatments to address these co-morbid conditions, paving the way for novel preventive and therapeutic interventions.